Self-consistent modelling of plasma density increase with radio-frequency heating - Moiseenko, V.Е.; Stadnik, Yu.S.; Lyssoivan, A.I. (Вопросы атомной науки и техники, 2012)
The self-consistent model of the radio-frequency (RF) plasma production in stellarators is described in this work. With this model of plasma production, one can perform calculations for different antenna systems. The selfconsistent model includes the system of the particle and energy balance equations and the boundary problem for the Maxwell’s equations. The numerical calculations of RF plasma production with four-strap antenna in the Uragan-2M stellarator are presented. Описана самосогласованная модель высокочастотного (ВЧ) создания плазмы в стеллараторах. С помощью этой модели создания плазмы можно проводить расчеты для различных антенных систем. Модель включает в себя систему уравнений баланса частиц и энергии, и краевую задачу для уравнений Максвелла. Представлены результаты численных экспериментов по ВЧ-созданию плазмы в стеллараторе Ураган-2М с использованием четырехполувитковой антенны с помощью разработанной модели. Описано самоузгоджену модель високочастотного (ВЧ) створення плазми в стелараторах. За допомогою цієї моделі створення плазми можна проводити розрахунки для різних антенних систем. Модель включає в себе систему рівнянь балансу частинок та енергії, та крайову задачу для рівнянь Максвелла. Представлено результати числових експериментів з ВЧ-створення плазми в стелараторі Ураган-2М з використанням чотиринапіввиткової антени за допомогою розробленої моделі.